Effect of basketball match simulation on peak torque and functional torque ratio of stabilizing muscle of the ankle - Castro, Alex (2012)
The aim of this study was to analyze the effect of Basketball match work simulation on peak torque (PT) of ankle evertor and invertor muscles and on eccentric evertor/concentric invertor torque ratio (EVEECC/INVCON). Ten healthy college basketball players, without mechanics or functional ankle instability performed a laboratory-based protocol representative of work rates observed during basketball match-play. The test was composed of a succession of intermittent physical effort equally distributed in four periods of 10 minutes each, considering the mechanical and physiological demands of a basketball match-play. Prior to the start of the trial (Evaluation 1) and after 2° (Evaluation 2) and 4° (Evaluation 3) period, the subjects performed five maximal isokinetic concentric and eccentric contractions of ankle invertors and evertors muscles, separated by two minutes rest, at 60 °/s and 120 °/s. After testing for normality of data distribution with the Shapiro-Wilk test, was used the ANOVA repeated measures and post-hoc Bonferroni test for comparison of variables between assessments. Was adopted p < 0.05. There was no significant difference for EVEECC/INVCON torque ratio between assessments. However, there was a decrease in PT EVEECC at 60º/s and 120º/s for the Evaluation 2 when compared to Evaluation 1. There was a reduction of PT INVCON values in relation to Evaluation 1, compared to Evaluation 2 at 60°/s and to Evaluation 3 at 120°/s. Given these results, we conclude that the progress of simulation basketball match-play lead a reduction on PT of the ankle evertors and invertors muscles. Key words: Sprains and Strains; Muscle Strength; Joint Instability; Isokinetic Dynamometer.